2022
DOI: 10.1007/s42729-022-01079-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress

Abstract: The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains (Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…The use of biochar has shown a significant improvement in the activities of antioxidant enzymes. The results are consistent with the research conducted by Nawaz et al 78 and Kumari and Malaviya et al 79 which showed that biochar can enhance the activities of antioxidant enzymes, hence strengthening the plant’s ability to defend against oxidative stress. Moreover, nanoparticles, as explored by Adrees et al 80 and Hussain et al 81 , have been shown to enhance the activities of antioxidant enzymes in wheat plants.…”
Section: Discussionsupporting
confidence: 92%
“…The use of biochar has shown a significant improvement in the activities of antioxidant enzymes. The results are consistent with the research conducted by Nawaz et al 78 and Kumari and Malaviya et al 79 which showed that biochar can enhance the activities of antioxidant enzymes, hence strengthening the plant’s ability to defend against oxidative stress. Moreover, nanoparticles, as explored by Adrees et al 80 and Hussain et al 81 , have been shown to enhance the activities of antioxidant enzymes in wheat plants.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, treatment with 200 µM SNP reduces the negative impact of salinity on the content of photosynthetic pigments (Figures 4 and 7). It is known that an increase in the content of photosynthetic pigments lead to an increase in plant biomass and productivity [45][46][47]. This is supported by the data in Table 3.…”
Section: Discussionsupporting
confidence: 62%
“…PGPMs have shown particular promise in combination with biochar in agricultural applications [ 49 , 50 ]. Combining biochar with PGPMs has been demonstrated to be of benefit to plants under drought stress, such as French beans [ 51 ], cucumber [ 52 ], maize [ 53 ], soybeans [ 54 ], and a range of other crops [ 55 ]. Prior research has also been conducted on the combination of biochar with compost [ 56 , 57 ], compost tea [ 58 ], and sewage sludge [ 10 ], which facilitate broad-spectrum microbial inoculation of biochar.…”
Section: Introductionmentioning
confidence: 99%